Climate Change, Adaptation, and Climate-Ready Development Assistance. (1st April 2014) - Light, Andrew; Taraska, Gwynne
Abstract : Traditional justifications for state-to-state development assistance include charity, basic rights and self-interest. Except in unusual cases such as war-reparations agreements, development assistance has typically been justified for reasons such as the above, without reference to any history of injury that holds between the states. We argue that climate change entails relationships of harm that can be cited to supplement and strengthen the traditional claims for development assistance. Finally, to demonstrate the utility of this analysis, we offer a brief application of our reasoning to the emerging conflict in the United Nations over the future post-2015 development agenda.